1995
DOI: 10.1139/z95-135
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution, habitat utilization, and social interactions of humpback whales,Megaptera novaeangliae, off Hawai'i, determined using acoustic and visual techniques

Abstract: Acoustic and visual methods were used to track and observe humpback whales off the island of Hawai'i. Sixty-two singing whales were located acoustically in water depths from 10 to 305 fathoms (mean 126 fathoms; 1 fathom = 1.828 m). This indicates that singers are not confined within the 100-fathom contour, although nearshore waters had a higher density of singers. The separation distance between singers (mean 5.1 km) was found to be significantly greater than that between nonsinging singletons (mean 2.1 km), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
175
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 31 publications
11
175
0
1
Order By: Relevance
“…Hence humpback males could be in the whole study area, shown in the overlap with mothers and calves groups. Moreover, the pods without calves could be occurring in same the locations frequented by singers, similar to what Frankel et al (1995) reported in Hawaii.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hence humpback males could be in the whole study area, shown in the overlap with mothers and calves groups. Moreover, the pods without calves could be occurring in same the locations frequented by singers, similar to what Frankel et al (1995) reported in Hawaii.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, distribution of male singers seemed to follow a similar pattern described by Whitehead and Moore (1982), they report singers in shallow isothermal water over to smooth bottom, where song propagation will be virtually bi-dimensional. However, singers elsewhere had been located on deep waters (Frankel et al 1995), where offshore locations provide different acoustics propagation conditions. Thus, the factor that determines which area is preferable may be social rather than oceanographic (Frankel et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant vocalizations are short, simple 'whup' calls, likely contact calls (Wild & Gabriele 2014) that could be rendered inaudible by vessel noise in a way similar to those documented for right whale calls (Clark et al 2009, Tennessen & Parks 2016). On the humpback whale's tropical wintering grounds, male humpback whales spend copious amounts of time on song displays integral to their mating system (Frankel et al 1995, Darling et al 2006, Herman 2017. Males are known to sing in late summer and fall in Glacier Bay (Gabriele & Frankel 2002) and it is speculated that high-latitude song on or adjacent to feeding areas may also be important to the reproductive success of individual males (Charif et al 2001, Gabriele & Frankel 2002.…”
Section: Biological and Behavioral Implications Of Sound Exposurementioning
confidence: 99%
“…Vessel noise has the potential to interfere with the complex vocal behavior of humpback whales, and thus could indirectly affect their population dynamics. Humpbacks produce a wide variety of vocalizations in many social contexts, which include the famous mating "songs" in their winter breeding grounds [4][5][6][7][8][9][10] as well as specialized "feeding calls" in their summer feeding grounds [11][12][13][14] that could serve as long-range assembly calls [2], likely coordinates group-feeding behavior and/or manipulate their prey (small schooling fish, [32]). Singing humpbacks are also known to modify their vocal behavior as a direct consequence of the vocal behavior of other humpbacks [5,8,15], most readily evidenced in the convergence of song acoustic structure among populations of males across each breeding season.…”
Section: Introductionmentioning
confidence: 99%